2011
DOI: 10.1002/jso.22122
|View full text |Cite
|
Sign up to set email alerts
|

Post‐radiation sarcomas. Clinical outcome of 52 Patients

Abstract: Prognosis of post-radiation sarcomas is poor; the type of the sarcomas is the only significant variable for survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 52 publications
(106 reference statements)
1
54
0
11
Order By: Relevance
“…We excluded patients with sarcomas originating in bone because evidence indicates that they have a different biology and survival than patients with STS. 13 A retrospective chart review was performed to extract clinical and pathologic information including patient age, date of sarcoma diagnosis, date of sarcoma resection, size of sarcoma, date of recurrence, and recurrence type (local/distant). For patients with RA-UPS/MFH, date of diagnosis for initial cancer, date of radiation, dose of radiation, and use of chemotherapy for primary malignancy were recorded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We excluded patients with sarcomas originating in bone because evidence indicates that they have a different biology and survival than patients with STS. 13 A retrospective chart review was performed to extract clinical and pathologic information including patient age, date of sarcoma diagnosis, date of sarcoma resection, size of sarcoma, date of recurrence, and recurrence type (local/distant). For patients with RA-UPS/MFH, date of diagnosis for initial cancer, date of radiation, dose of radiation, and use of chemotherapy for primary malignancy were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…7,12 However, more recent evidence suggests that this period may be much shorter for soft tissue sarcoma (STS). 9,11 Whereas the latency period for bone sarcoma is reported to be as long as 15 years, 13 the latency period for STS is commonly reported to be 7–16 years. 810,14,15 …”
mentioning
confidence: 99%
“…This risk is delayed by an average of approximately 15 years. 34,35 However, the ICRP method is explicitly not intended for prediction of risks from therapeutic radiation. 25 It provides an estimate of global population risk, irrespective of age.…”
Section: Estimating Risk From Radiotherapymentioning
confidence: 99%
“…In addition, recent findings from studies on Japanese atomic bomb survivors have suggested that the risk of sarcomas is elevated by acute lower doses of radiation (<5 Gy) at any age 11. Osteosarcoma is the most common type of post- radiation sarcoma, followed by malignant fibrous histiocytoma and fibrosarcoma 14. The good absorption of radiation by bone may account for the high incidence of bone sarcoma relative to other sites.…”
Section: Epidemiologymentioning
confidence: 99%